Chronic monocytic leukemia with transformation into acute monocytic leukemia - I.S. Shponka; L.A. Pesotskaya; H.S. Korolenko; I.O. Hutnik; B.V. Murashevych; V.A. Nikonenko (Medičnì Perspektivi)
Chronic myelomonocytic leukosis (CMML) is rarely diagnosed and amounts to 1 per 100 thousand of adults per year, more often in men over 60 years.  The clinical case of the rare, prolonged course of myelodysplastic chronic myelomonocytic leukosis (MD-CMML) in a middle-aged woman with rapid transformation into acute monocytic leukemia (AMoL-M5в) with the atypical fulminant course is presented. A retrospective analysis of the course of the disease drew attention to the severe vasculitis suffered by the patient 19 years ago, which could be regarded as the debut of CML in the presence of characteristic pathological changes in the hemogram. Non-pronounced clinical manifestations in the form of moderate cervical lymphadenopathy, skin lesions in the form of transient erythema, spotty eruptions over the next 10 years, fit into the clinical picture of MD-CMML. A detailed picture of the disease was observed after viral infection, bronchitis, antibiotic therapy. Absence of significant blastemia and severe inhibition of normal hematopoiesis with expressed extramedular manifestations of the disease in the patient were not typical for the course of AMoL-M5b in this case. The progression of skin lesions was noteworthy, which gave reason for unfavorable prognosis.  For several weeks, the spread of erythematous elements was observed throughout the body with itching, not controlled by antihistamines and corticosteroid drugs; the appearance of maculopapular rashes, merging in places; small-point hemorrhages like vasculitis over the entire surface of the skin. Notable was the development of severe hemorrhagic syndrome without severe thrombocytopenia, significant changes in the coagulogram, as a manifestation of early severe coagulopathy.